Alzheimer’s disease-related a-synuclein gene expression in CA3 subfield of hippocampus in post-ischemic brain during 2-year survival - Pluta, Ryszard; Bogucka-Kocka, Anna; Bogucki, Jacek; Kocki, Janusz; Czuczwar, Stanisław (Folia Neuropathologica, 2025)
In this study, we investigated whether changes in the expression of the a-synuclein gene occur and participate in post-ischemic brain neurodegeneration of Alzheimer’s disease phenotype. The current study assessed the expression of the a-synuclein gene by RT-PCR after 10-minute brain ischemia in rats in CA3 area with survival at 2, 7, and 30 days and 6, 12, 18, and 24 months. Reduced gene expression was observed at 2 days, 6, and 24 months after ischemia. In the remaining observation periods, i.e., 7 and 30 days and 12 and 18 months, its expression was significantly above control values. In post-ischemic brain, where survival times ranged from 2 days to 2 years, we noted biphasic changes in overexpression of the a-synuclein gene in the CA3 area of the hippocampus. The presented data correlate very well with previous studies, which found an increase in protein levels in the brain and strong immunostaining for a-synuclein after ischemia. Finally, the results clearly indicate that changes in the expression of the a-synuclein gene play an important role in acute and secondary brain injury and the development of brain neurodegeneration after ischemia of Alzheimer’s disease phenotype. Overall, studies show that a-synuclein is an attractive target for the development of new therapies to minimize ischemic brain damage and neurological dysfunction.